Persepsi Masyarakat Terhadap Pelecehan Seksual di Media Sosial (Studi Kasus: Komentar Negatif pada Akun Azizah Shalsa) - Arislawati Lintang Azhari; Laila Miftahul Janah; Febriansyah; Zakia Salsabila; Rio Kurniawan (JOSH: Journal of Sharia, 2025)
The development of social media has provided a new space for social interaction, but also brings challenges in the form of online gender-based violence. One form is sexual harassment in the form of negative comments on social media. This study aims to determine public perceptions of sexual harassment on social media through a case study of negative comments on the account of Azizah Shalsa, a young influencer in Indonesia. The research method used is a descriptive qualitative approach with observation techniques, in-depth interviews, and documentation studies. The results of the study show that sexual harassment is still not considered a serious issue by some people, especially due to gender bias, low digital literacy, and lack of legal awareness. Therefore, this study emphasizes the importance of public education and law enforcement to create a safe and fair digital space.